Hubungan Aktivitas Fisik dengan Tingkat Nyeri Otot pada Usia Produktif di Puskesmas Banguntapan II Bantul - Sabrina, Rizqa Nur (Badan Perencanaan Pembangunan Daerah Kabupaten Bantul, 2021)
The level of muscle pain is an unpleasant emotional and sensory experience that results in the risk of damage due to the use of muscles that are too tense and excessive. In 2018 the most severe cases of muscle pain were in the Banguntapan 2 Primary Health Center of Bantul with 2,634 cases and the highest percentage occurred in the productive age (50.91%). The average physical activity carried out at productive age in Indonesia is 86.6% by farmer / laborer / fisherman job. That results in excessive activity or a high repetition rate. If not handled properly, muscle pain causes stiffness in the muscles, impedes work and other daily activities, decreases quality of life and causes chronic pain that is able to affect 11-24% of the world population in a few days, months and even years. This research was conducted with the aims to determine the correlation between physical activity and the level of muscle pain in productive age. This research was a quantitative correlation with the cross sectional time approach, and using a questionnaire as an instrument. The sample used purposive sampling with 51 respondents. The data analysis used Kendall Tau. Kendall Tau correlation test results between physical activity and the level of muscle pain obtained significance value (p-value) of 0.000 <0.05. There is a correlation between physical activity and the level of muscle pain in the productive age at Banguntapan 2 Primary Health Center in Bantul. The respondents should keep doing active physical activity correctly by stretching between working hours and regular exercise.